Microbiological, inmunological and biochemical features of mechanical ventilation-associated neumonia (MICROVAP) development (2024)
This study focuses on the complex relationship between positive pressure mechanical ventilation, the pulmonary microbiome, cytokine dynamics, and metabolomic profiles in patients with ventilator-associated pneumonia (VAP). Our research emphasizes how alterations in microbial dynamics are associated with the onset of VAP, underscoring the pivotal role of microbiomes in maintaining respiratory health, particularly in the context of viral respiratory diseases such as COVID-19. We observed significant variations in microbial abundances, which have implications for the development and progression of VAP. Furthermore, our analysis of cytokine dynamics revealed a distinctive immunological modulation in VAP patients, characterized by an enhanced response of neutralizing antibodies coupled with reduced levels of proinflammatory cytokines.